Clarifying the conceptual map of VUCA: A systematic review - Taskan, B. (2022)
Purpose – Over the last few decades, the environment for organisations has been frequently described using the acronym VUCA: a volatile, uncertain, complex, and ambiguous environment. Despite the popularity of this acronym, it is not unusual to find some overlap concerning the meaning of those terms, as well as poor definitions of each in the literature. Consequently, the main aim of this paper was to conduct a systematic literature review to obtain a conceptual map of the components of VUCA and their relationships and to highlight some avenues for future research. Design/methodology/approach – We conducted a systematic review of various databases between 1999 and 2021. A total of 833 papers were identified and 26 of them met the inclusion criteria for the current study. Findings – The subsequent analysis revealed several overlaps and relationships between the four terms. Based on this analysis, we propose a conceptual map that could serve as a basis for future research and practice. Research limitations – Due to the exploratory nature of the study and the scarce number of empirical studies, the impact that the use of the VUCA framework has had on businesses could not be addressed. Originality – By clarifying the different components of VUCA and specifying the relationships between them with a comprehensive conceptual map, this paper may contribute to more rigorous empirical research, as well as help managers and executives more effectively deal with turbulent environments.